Preparation and characterisation of treated agricultural wastes as biosorbents - Siti Nor Sihariddh, binti Samsudin (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This study characterizes the agricultural wastes i.e., coconut husk, banana trunk, sago hampas, rice husk and oil palm empty fruit bunch treated with sulfuric acid (H2S04) and sodium hydroxide (NaOH). The pretreatment was done to improve the adsorption capacity and enhance the porosity structures. The physicochemical properties, functional characteristics and morphological structure of treated biomass were characterized. The treated samples were characterized by a low pH with high ash content. Principal Component Analysis (PCA) suggested that the treated and untreated samples are distinguishable with acid and alkali treated coconut husk demonstrating similar functional characteristics. Morphologically, the treated samples showed better developed microporous structures.